Physiology and acclimation potential are tuned with phenology in larvae of a prolonged breeder amphibian. Issue 3 (6th December 2021) - Enriquez‐Urzelai, Urtzi; Nicieza, Alfredo G.; Montori, Albert; Llorente, Gustavo A.; Urrutia, Miren Bego
Abstract : Due to the speed of climate changes, rapid buffering mechanisms such as phenotypic plasticity – which may depend on breeding phenology – could be key to avoid extinction. The links between phenology and plasticity, however, remain understudied. Here we explored the matching between phenology and the thermal sensitivity of standard (SMR) and routine metabolic rates (RMR), metabolic scope (i.e. the difference between RMR and SMR), survival and growth‐development trajectories in larvae of a prolonged breeder amphibian Alytes almogavarii acclimated to 10 and 20°C, belonging to three cohorts: autumn pre‐overwintering, autumn overwintering and spring tadpoles. At 20°C, survival of autumn pre‐overwintering larvae was lower than for the rest. Although all cohorts showed acclimation potential, patterns for SMR and RMR differed, leading to differences in metabolic scope. Regardless of temperature, overwintering tadpoles arrested growth and development, while pre‐overwintering and spring tadpoles showed higher growth and development at 20°C. At 10°C pre‐overwintering tadpoles allocated more energy to development compared to spring tadpoles to advance development before winter. Overall, we demonstrate that the effects of temperature depend on phenology, consistent with future, expected thermal regimes. This suggests that extreme events can yield different vulnerability to climate change within populations (e.g. associated to discrete within‐year cohorts), and not only between species or populations.